Preparation and in vitro evaluation of floating tablets using biodegradable polymers - C. HARANATH; J.RAVEENDRA REDDY; N.DEVANNA (International Journal of Pharma and Bio Sciences, 2017)
Floating tablets of furosemide were prepared using Albizia gum, Dammar gum and Copal gum as polymers for controlling the drug release. Furosemide is poorly water-soluble drug (Class IV) and its bioavailability is very low from its crystalline form. The rate of absorption and the extent of bioavailability for such insoluble drug are controlled by the rate of dissolution in the gastrointestinal fluids. Hence, number of attempts were made to increase the rate of dissolution of such poorly water soluble drugs, to increase their effectiveness and simultaneously reduce their doses and hence the toxic effects. Two types of diluents were used and the drug release was compared. Pure drug and optimized formulation were subjected to the drug excipient compatibility studies using FTIR and DSC. The studies revealed that there was no interaction between the drug and excipients. In order increase the drug release channeling agents were introduced namely Lactose and DCP. Lactose is water soluble diluent and DCP is water insoluble diluent. Precompression parameters were performed to all the formulations and were found to be in the acceptable limit which ensures the good flow properties. Formulation FFRA4 containing albizia gum and lactose as channeling agent showed good results when compared with other formulations. The floating lag time of the optimized formulation was very short and the percentage of drug release at the end of 12 hours was found to be high. The drug release kinetics revealed that formulation FFRA4 follows zero order kinetics and the mechanism was nonfickian.